HISTOPATHOLOGICAL MANIFESTATION IN GALLUS GALLUS DOMESTICUS INFECTED WITH CESTODE PARASITE (International Journal of Food and Nutritional Sciences, 2022)
In the present investigation on histopathology of Gallus gallus domesticus infected from cestode parasite, Amobetanea sp. The cestode worm attaches to the host tissue and ingests the food. The worm is linked to the mucosal layer, according to the T. S. of the gut. The gut mucosal layer was disrupted and seemed to be damaged as a result of its attachment. It also shows hemorrhages, nodular growth, lesions, eroded mucosal epithelium, and ulcerations. Moreover, Intestinal mucosa was damaged and eroded as a result of the parasites' attachment, which may have favoured additional bacterial infections that led to greater inflammation and severe cellular reactions in the affected area